Differences in Knowledge Level of Academic and Internship Students on the Prevention of Healthcare Associated Infections (HAIs) - Utami, Khansa Salsabila Wahyu Widyan; Wantiyah, W; Purwandari, Retno (Jurnal Berita Ilmu Keperawatan, 2022)
Among healthcare workers, nurses are the ones most contacted with patients and infectious materials in the nursing room. Nurses lack of knowledge factors can lead to HAIs. Therefore, it’s important for nursing students who have not practiced or have practiced in hospitals to understand how to prevent HAIs. The aim of this study was to analyze the difference in knowledge levels of academic nursing students and professional nursing students in prevention. This study used descriptive design with comparative analysis. Total participant is 298 nursing students consisted of 196 academic nursing students and 102 professional nursing students were gathered with total sampling technique and statistic test used Mann Whitney. The results showed there aren’t a difference in knowledge level of the academic nursing students and professional nursing students, on the indicator of knowledge about HAIs (p= 0,619), on the indicator of knowledge about standard precautiom (p= 0,459), and there is a difference on the indicator of knowledge about hand hygiene (p= 0.001). Almost all respondents have good knowledge about HAIs. Knowledge of HAIs is very important to learn, with the aim that nursing students can avoid exposure to HAIs, and can apply HAIs prevention and control when practicing in healthcare settings